Dinâmica de partículas irregulares - Straatmann, Vitor (2023)
This work aims to analyze the influence of particle shape on their fluidodynamic behavior and industrial equipment. Firstly, a theoretical approach is presented on how particle shape is characterized, including its traditional parameters and their consequent influence on the behavior of particulate beds. Several experimental studies and numerical simulations were evaluated, with a focus on parameters related to particle shape. The results highlighted the importance of these parameters in accurately describing the behavior of particles in multiphase systems, affecting flow resistance, dispersion, agglomeration, and sedimentation. Proper consideration of these parameters can optimize the efficiency of industrial equipment. However, challenges such as the complexity of particle-fluid interactions and the diversity of particle shapes and sizes require further investigation and ongoing experimental validation.